Water resources data and information exchange in transboundary water treaties - Gerlak, A.K.; Lautze, Jonathan F.; Giordano, Mark (Springer, 2011)
Despite international calls for data and information sharing in transboundary waters and basin-specific evidence of its importance to cooperative management, no systematic research has been undertaken to answer questions of where, how frequently, and which water resources data and information are exchanged. This paper examines all available transboundary water agreements signed between 1900 and 2007 to determine the degree to which water resources data and information is exchanged in the world's regions, how the level of exchange has developed over time, and the different ways in which data and information sharing has been codified in practice. In doing so, we reveal important trends regarding the mechanisms, types, and frequencies of water resources data and information sharing?as well as differences across temporal and spatial scales, by treaty type and function, and regime type. The results indicate that data and information exchange as already practiced is more nuanced and, in some senses, widespread than may commonly be recognized. Further, the results reveal key linkages between democracy and data and information exchange and provide a basis to test analogous linkages related to data sharing and other variables in transboundary water settings.